Fuzzy Controller for Solar Cell Optimization. (August 2019) - Azmi, Zulfian; Mawengkang, Herman; Zarlis, Muhammad; Tulus,; Efendi, Syahril
Abstract: This study describes the Fuzzy Logic Control for the movement of Solar Cells that use fuzzy logic algorithms to achieve intelligent and flexible knowledge-based systems in the design of hardware to achieve efficiency in controlling the movement of solar cells that are better and maximize the function of the solar cell motor works based on time input. Fuzzy Logic allows mapping from the input given based on time to an output. involves components of variables, membership functions, Fuzzy Logic operators and if-then rules. And with an analysis it can produce optimum output of Solar cell rotation.